Individualized network analysis: A novel approach to investigate tau PET using graph theory in the Alzheimer’s disease continuum - Protas, Hillary; Ghisays, Valentina; Goradia, Dhruman D.; Bauer, Robert; Devadas, Vivek; Chen, Kewei; Reiman, Eric M.; Su, Yi (Frontiers in Neuroscience, 2023)
Tau PET imaging has emerged as an important tool to detect and monitor tangle burden in vivo in the study of AD. Previous studies demonstrated the association of tau burden with cognitive decline in probable AD cohorts. This study introduces a novel approach to analyze tau PET data by constructing individualized tau network structure and deriving its graph theory-based measures. We hypothesize that the network based measures are a measure of the total tau load and the stage through disease. Using data from the Alzheimer’s Disease Neuroimaging Initiative, we demonstrate that the derived network measures are able to differentiate three clinical stages of AD, cognitively unimpaired, MCI and AD. We also demonstrate that these network measures are strongly correlated with regional tau burden measures and memory performance overall. Unlike regional tau measurements, the tau network measures were significantly associated with auditory verbal learning test for long-term recall memory (AVLT-LTM) scores even in cognitively unimpaired individuals, suggesting the proposed technique may be used to characterize subtle early tau accumulation. Stages determined from global efficiency and limbic strength, visually resembled Braak staging. Further investigation is ongoing to examine this technique in a longitudinal setting.